Komitmen Beribadah Mahasiswa dalam Konteks Gaya Hidup Kampus, Tekanan Akademik, dan Lingkungan Sosial: Suatu Tinjauan Literatur - Hamka, Buya (MACCA : Science-Edu Journal, 2025)
This article presents a literature review aimed at identifying and analyzing the factors that influence students’ commitment to religious practices, particularly in the context of campus lifestyle, academic pressure, and social environment. Using a systematic review of twelve accessible and nationally recognized journal articles, the study reveals that students' spiritual dynamics are significantly shaped by their modern lifestyle, high academic demands, and the social atmosphere of the university. Findings indicate that students who are part of religious communities, possess effective time management skills, and receive consistent spiritual guidance tend to maintain a more stable commitment to worship. Conversely, disorganized lifestyles and permissive social environments hinder the consistency of religious observance. These findings align with social learning theory and religious coping frameworks, offering a comprehensive perspective on religious behavior among university students. This review is expected to serve as a reference for higher education institutions in designing data-driven and integrated spiritual development programs